Imperial-Colonial Discourses and the Politics of English Language in the 19th Century English Novels: Joseph Conradâs Lord Jim (1992) and Rudyard Kiplingâs Kim (1993) - Nurrachman, Dian (ASPENSI in Bandung, Indonesia, 2017)
ABSTRACT: The position of English literature, especially its novels in the 19th century as the proponent of English imperialism-colonialism, proved that literature â as another discipline as well â would not be an innocent discipline, and never has been. English literature was then placed as the hegemonic power, which manifested in the imperial-colonial discourses to sustain imperialism-colonialism, since the power of its content can leave an influence behind the colonized people. From this stance as well, then, the politics of English language appeared to accompany the imperial-colonial discourses. The politics of English language in English literature was the foremost notion of English language growth or expansion all over the world, which is nowadays known by several names, such as Global English(es), World English(es), and English as an International Language. The result of the research showed that the two novels, âLord Jimâ written by Joseph Conrad (1992) and âKimâ written by Rudyard Kipling (1993), were indeed the imperial-colonial texts which reflected and represented the imperial-colonial discourses and the politics of English language within their narratives. In the imperial-colonial discourses, the two novels represented the characteristics of hegemony and power, hybrid cultural identity, and politics of difference and racism which representatively existed there, as well as the ideological interests of their narratives to be a system of statements (theorizing knowledge) which theorizes the colonized (indigenous) people. KEY WORDS: English Literature; Imperialism; Colonialism; Discourse; Politics of English Language. About the Author: Dian Nurrachman, M.A. is a Lecturer at the Department of English, Faculty of Adab and Humanities UIN SGD (State Islamic University, Sunan Gunung Djati) Bandung, Jalan A.H. Nasution No.105 Cipadung, Bandung 40614, West Java, Indonesia. For academic interests, the author is able to be conducted via e-mail at: diannurrachman@gmail.comÂ How to cite this article? Nurrachman, Dian. (2017). âImperial-Colonial Discourses and the Politics of English Language in the 19th Century English Novels: Joseph Conradâs Lord Jim (1992) and Rudyard Kiplingâs Kim (1993)â in TAWARIKH: International Journal for Historical Studies, Vol.8(2) April, pp.153-162. Bandung, Indonesia: Minda Masagi Press and UIN SGD Bandung, ISSN 2085-0980.Chronicle of the article: Accepted (March 11, 2017); Revised (April 5, 2017); and Published (April 28, 2017).